Effectiveness of Instructional Program Regarding Health Protective Behaviors for Women with Gestational Diabetes on their Self Efficacy in Primary Health Care Centers at Baghdad City - Sagdh Hameed Kareem; Iqbal Majeed Abbas (Institute of Medico-legal Publications Pvt Ltd, 2021)
Objective: The present study to identify the relationship between these pregnant women’s their selfefficacy study variables. -and determine the effectiveness of Gestational Diabetes health protectivebehaviors-oriented Instructional program on their self-efficacy .Methods: A descriptive analytic study ( two-groups Pretest- Posttest)used to determine the Effectivenessof Instructional Program Regarding Health Protective Behaviors for Women with Gestational Diabeteson Their Self Efficacy on Pregnancy Outcome in Primary Health Care Centers at Baghdad City.